Polybutylene terephthalate for laser-based powder bed fusion of polymers: processing constraints driven by zero-shear viscosity - Cholewa, Simon; Forstner, Thomas; Jaksch, Andreas; Drummer, Dietmar (Progress in Additive Manufacturing, 2025)
Laser-based powder bed fusion of polymers (PBF-LB/P) is a layer-based additive manufacturing (AM) method that produces functional components with superior mechanical properties. However, the limitation of commercially available materials, primarily polyamides, reduces the range of applications for PBF-LB/P processed parts. The use of novel polymer feedstocks, such as polybutylene terephthalate (PBT) in PBF-LB/P is of great interest, as the properties of PBT allow for an extension of the application of AM-built parts in the automotive and electronics sectors. Studies on the flowability of the powder under process conditions at evaluated temperatures showed a homogeneous surface of the powder bed. In addition, the processability of PBT powders in the PBF-LB/P process was investigated with a thermal camera, showing process limits for low-viscosity materials. Component properties showed a higher Young’s modulus than injection molding, while fracture behavior showed brittle behavior for the homo-PBT tested.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Additive manufacturing; Balling; Morphology; Powder bed fusion; Zero-shear viscosity